Evolução biológica e mídia-educação: problematizando uma sequência didática - Camargo, Blendon Dias (2023)
The present study constructed and analyzed a didactic sequence (DS) in science education that, associated with critical perspectives in education, was built on two axes: biological evolution and media education. Working with these two axes, this study proposes a praxis beyond the curriculum in that it considers critical and reflective dimensions in the relationships between Technology, Science, Society, Environment, and, more specifically, media. Based on this, the possible contributions of this DS to the teaching and learning process in the final years of elementary school were discussed, understanding that there are potentials related to student protagonism, dialogicity, autonomy, group work, creativity, and critical thinking. This study is qualitative, using field observations, questionnaires, and analyses of the material produced by students. The data showed that the vast majority of students had no knowledge of biological evolution and used non-scientific sources of information to explain biodiversity. In contrast, at the end of the DS, students criticized sources that spread misinformation and used evolution concepts to counter fake news. Finally, it was observed that the association between evolution and media occurred with positive results because, with autonomy, students put this into practice in the last activity of the DS, revealing that the concepts related to the two themes were learned, articulated, and applied critically.